METHODOLOGY FOR DEVELOPMENT OF LEADERSHIP SKILLS OF MANAGERS - Rakhimova , Dilrabo Oktyabrovna (Educational Research in Universal Sciences, 2023)
Formation of leadership skills of future managers in the article. The role of leadership ability in the work of managers and its effect on the useful work coefficient, aspects that should be paid attention to in increasing leadership potential were discussed.